Bioabsorbable Unsintered Hydroxyapatite/Poly-l-Lactic Acid Pin Fixation of Osteochondritis Dissecans in Adolescents: Initial Experiences - Zeilinger, Martin Georg; Autenrieth, Christian; Remmel, Kerstin; Schuh, Alexander; Hammon, Matthias; Schraml, Annemarie; Uder, Michael; Rompel, Oliver (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
Background This study sought to retrospectively evaluate the clinical and magnetic resonance imaging (MRI) outcomes of u-HA/PLLA pin (u-HA/PLLA: hydroxyapatite/poly-L-lactic acid) pin fixation of unstable osteochondritis dissecans (OCD) lesions of the knee.Methods Seven adolescent patients (four females and three males) with arthroscopically unstable OCD lesions of the knee were included. The mean age at diagnosis was 13.1 years. Clinical results were evaluated preoperatively and during follow-up using the Ogilvie-Harris score (0 – 15 points). MRI scans were performed preoperatively and during follow-up, with results evaluated using the Dipaola classification (grades 1 – 4). Mean follow-up time was 29 months.Results The median Ogilvie-Harris score improved from 13 points (range: 10 – 14 points) to 15 points (range: 13 – 15 points). Separately, the median Dipaola score improved from 3 points (range: 2 – 4 points) to 1 point (range: 1 – 4 points). No complications such as infection, synovitis, or intra-articular adhesion were observed.Conclusions Initial experiences using bioabsorbable u-HA/PLLA pins for the refixation of unstable OCD lesions in adolescents in the knee are promising, and MRI provides excellent monitoring of healing.
Keywords: Osteochondritis dissecans; juvenile; u-HA/PLLA; bioabsorbable pins